2013
DOI: 10.1002/aic.14241
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of granular particles by mass, radius, and density in a horizontal rotating drum

Abstract: The impact of particle properties on segregation and mixing of bidisperse granular beds in a rotating horizontal drum have been studied by discrete element method (DEM) simulations. Bidispersities in radius, density, and mass have pronounced influences on the stationary mixing pattern, although they hardly affect the granules' flow regime. At 50% fill level, all beds mix well for a Froude number of ∼0.56, corresponding to a flow regime intermediate to cascading and cataracting, while segregation occurs both at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…Jain et al [1,27] studied the behavior of granular mixing and segregation by combining the size and density effects of a binary mixture in a thin rotating drum. Arntz et al [9] reported that three parameters predominantly determined the segregation behavior; namely, differences in the radius, density, and mass, which they found to be related to percolation, buoyancy, and inertia mechanisms, respectively. Granular materials may also segregate spontaneously in a regular streak segregation pattern.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Jain et al [1,27] studied the behavior of granular mixing and segregation by combining the size and density effects of a binary mixture in a thin rotating drum. Arntz et al [9] reported that three parameters predominantly determined the segregation behavior; namely, differences in the radius, density, and mass, which they found to be related to percolation, buoyancy, and inertia mechanisms, respectively. Granular materials may also segregate spontaneously in a regular streak segregation pattern.…”
Section: Introductionmentioning
confidence: 97%
“…Two regions are observed in the granular motions in a rotating drum with partially filled containers: a fixed bed region and a flowing layer region at a free surface where the mixing and segregation of granular matter occur. Core segregation typically occurs in a binary mixture with different sizes or densities in a rotating drum because of percolation and buoyancy effects [1,3,[9][10][11][12]27,28]. Jain et al [1,27] studied the behavior of granular mixing and segregation by combining the size and density effects of a binary mixture in a thin rotating drum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Article [11] presents results of numerical modeling of a three-dimensional non-established flow of active layer of granular particles under the rolling over mode, which was based on the theory of Euler biphase flow and kinetic theory of granular flow. An intermediate, between the cascade and cataract modes, granular flow at the values of filling degree of a chamber at 0.5 and the Froude number of 0.56, employing the method of discrete elements, was examined in [12]. Results of testing and verifying the source data, with the application of the method of discrete elements, for modeling the motion of granular fill in a rotating chamber, are presented in [13].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Studies of particles segregation in rotating drums have long history since 1939 (Oyama, 1939). Researchers used particles of different sizes, masses, densities, shapes and elasticities to experimentally investigate segregation in dry rotating drums (Kuo et al, 2006a;Arntz et al, 2014) or in drums with different interstitial fluids (Chou et al, 2010). Numerically studies of particle flows/segregation in rotating drums are also conducted by a number of groups using DEM and CFD (Marigo et al, 2012;Huang et al, 2013a;Alizadeh et al, 2014;Marigo and Stitt, 2015).…”
Section: Introductionmentioning
confidence: 99%